The Administrative Burden Experienced by U.S. Rural Residents Accessing Social Security Administration Benefit Programs in 2024 - Debra L. Brucker; Stacia Bach; Megan Henly; Andrew Houtenville; Kelly Nye-Lengerman (Social Sciences, 2025)
Grounded in the existing literature on administrative burden and using a qualitative and community-engaged research approach, the research examined the administrative burden experienced in accessing disability, retirement, and survivor benefits from the Social Security Administration (SSA). The research team held in person and virtual focus groups and interviews with 40 adults with disabilities, older adults, and family members of people with disabilities who resided in rural areas of the U.S. State of New Hampshire in 2024. The qualitative analysis revealed that rural residents, regardless of type of SSA benefit receipt, were experiencing high levels of administrative burden in their interactions with the SSA and preferred to turn to in-person assistance at local SSA field offices (rather than phone, mail, or web-based service options) to address these concerns. Overall, people living in rural counties that do not have local SSA field offices voiced a distinct disadvantage in terms of knowing where to turn with questions about their benefits. A lack of ready and reliable access to information and advice led to endangering their own economic stability and to increased calls and visits to the SSA. Persons with stronger social networks were better able to overcome these barriers to services.